Exploring the key points and key shots in table tennis matches based on survival analysis - Muzi Li; Qing Yang (PLoS ONE, 2026)
This study aimed to investigate the Key Points ( KP ) and Key Shots ( KS ) in singles matches for elite table tennis players, enhancing the knowledge of winning patterns in table tennis. A total of 60 men’s singles and 64 women’s singles matches were analyzed, all data sourced from events such as the World Championships, World Cup, Olympic Games, and WTT Champions. Methods: Survival analysis was introduced, in which points scored in a match and shot counts in a rally were treated as “survival time,” while losing a point was defined as the “event.” The Kaplan-Meier method was employed to estimate cumulative survival probabilities, which reflect the likelihood of players enhancing their winning potential at specific scores or shot numbers. The point or shot number at which the cumulative survival probability drops to 50% is defined as the KP or KS , respectively. Additionally, the Log-rank (Mantel-Cox) non-parametric test was applied to determine whether significant differences existed between the survival curves of different groups. Results: KP in table tennis singles demonstrate a stable pattern of “ 7 for women, 8 for men,” while Winning Points ( WP ) are predominantly concentrated at the 9th point. The KS positions are consistent in both men’s and women’s singles, specifically the 4th shot in the total rally, the 3rd shot in the serving round, and the 2nd shot in the receiving round. Winning Shots ( WS ) consistently occur at the 6th shot in the total rally, as well as the 3rd shot in both the serving and receiving rounds. Conclusion: These findings advance our understanding of winning patterns in table tennis, providing theoretical foundations and practical references for designing contextualized training programs, precisely regulating athletes’ competitive psychology, and optimizing future competition rules.